Pengaruh Stres Kerja dan Persepsi Dukungan Organisasi Terhadap Produktivitas Karyawan yang di Mediasi oleh Self-Efficacy (Studi Pada Karyawan My Creative.Id Yogyakarta) - Ersary Purwaningtyas; Epsilandri Septyarini (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study was structured to determine the effect of job stress and perceived organizational support on employee productivity mediated by self-efficacy. Both job stress, perceived organizational support and self-efficacy are the main factors affecting employee productivity in a company. The purpose of this study itself is to test the variables of job stress, perceptions of organizational support, self-efficacy and productivity of employees who work at MY Creative.Id Yogyakarta, researchers took samples by applying a non-probability method with a saturated sample. The questionnaires that were processed were 50 employees. The results in this study indicate that: (1) Job Stress has a negative effect on employee productivity, (2) Perceptions of Organizational Support have a positive and significant effect on Employee Productivity, (3) Job Stress has a negative effect on Self-Efficacy, (4) Self-Efficacy. Efficacy has a positive and significant effect on Employee Productivity, (5) Perceptions of Organizational Support have a positive and significant effect on Self-Efficacy, (6) Self-Efficacy does not mediate Job Stress on Employee Productivity, (7) Self-Efficacy mediates Perceptions of Organizational Support on Productivity Employees.